Architectural Diagram for Educational Games on Agile Methodologies - Aragao, Paulo Andre Pimenta [UNESP]; Souza, Rogeria Cristiane Gratao de [UNESP]; Rocha, A.; Goncalves, R.; Penalvo, F. G.; Martins, J. (Ieee, 2021)
For software development to be conducted in an organized manner, contributing to the quality of the final product, it is necessary to train professionals in the correct use of Software Engineering concepts and their development methodologies. Among them, the agile philosophy stands out for its acceptance of changes, with Scrum and Extreme Programming being the most used agile methodologies today. However, the teaching of this philosophy in the undergraduate courses, including the specificities involving each agile methodology, faces challenges given the vast theoretical framework involved, which can cause demotivation in students. Educational games have proven to be effective in the teaching-learning process of Software Engineering in general. Although, current solutions still have some deficiencies, such as the lack of games involving the comparison between different agile methodologies, to enable future professionals to select the best one for specific projects. Therefore, this paper proposes a software architecture to guide future implementations of quality educational games to teach agile methodologies since it remedies deficiencies detected through an empirical analysis involving available common purpose games.
Keywords: Agile Methodologies Learning; Educational Game; Software Architecture